The physiological nature of mental fatigue: current knowledge and future avenues for sport science - Roelands, B.; Kelly, V.; Russell, S.; Habay, J. (International Journal of Sports Physiology and Performance, 2022)
"Fatigue" is described as a physiological destination, a perception or emotion, and an important mechanism to minimize physical injury, but also as an experimental concept, a symptom, a risk, a cause, and a consequence.1 This abundance of definitions and concepts of fatigue is due to the widespread dissemination and overall division of this phenomenon throughout different research fields and professions. In a sport and exercise science context, which is the focus of the International Journal of Sports Physiology and Performance (IJSPP), fatigue is an elusive concept that can be induced both cognitively and physically. The twin domains of fatigue have important implications for human performance.